Challenges of Halal Certification for Floating Stall Entrepreneurs - Putri Pratama, Chici Rima; Hilian Batin, Mail; Mulki Octadyla, Malikal; Herlinia, Sella (Journal of Business and Economics Research (JBE), 2025)
This study identifies the key challenges faced by floating stall entrepreneurs at Benteng Kuto Besak Palembang in complying with mandatory halal certification. Using a qualitative descriptive approach, data were collected through in-depth interviews with two business owners and analyzed using thematic analysis. The findings reveal that despite the entrepreneurs' belief in their products' halal status, none have obtained certification. The primary challenges include: (1) a critical lack of awareness regarding the certification procedure and the government's free self-declare program, (2) difficulties navigating the online SIHALAL registration system, and (3) an absence of guidance from halal assistants (Pendamping PPH). The study concludes that enhanced targeted socialization, dedicated on-ground mentoring, and a simplified digital registration process are crucial to facilitate certification. These measures are essential for integrating these micro-enterprises into Indonesia's formal halal economy, thereby improving their market competitiveness and ensuring consumer protection.